SISTEM PAKAR DIAGNOSA PENYAKIT IKAN BERBASIS WEB MENGGUNAKAN METODE CERTAINTY FACTOR - Muhammad Khoirur Rozikin; Danang Mahendra; Agus Subhan Akbar (Journal of Information System and Computer, 2023)
In Jepara Regency, there are many fish sellers and breeders/cultivators. In the process of captive fish, usually fish cultivators will experience several problems, one of which is the emergence of disease in fish cultivated by fish cultivators. Prevention is a very effective step to minimize the risk of disease in farmed fish. If the fish are already diseased, the costs incurred for fish cultivation will increase due to the additional cost of fish treatment. Fish breeders need to know about fish diseases and how to treat them if the fish they farm are infected with diseases or pests. One of the efforts that can be done by fish breeders is by visiting fish disease experts (experts) which cannot be done continuously because it requires a lot of time, effort and money. From these problems, the author will create a website-based expert system for diagnosing fish diseases using the Certainty Factor method. With this application, it is hoped that it can assist fish breeders in dealing with diseases in protected fish, without having to visit an expert. In the author's research, testing was carried out based on 10 diagnostic samples, and calculated using k-fold cross validation, resulting in a system accuracy of 90%. Where the expert system that has been made by the author is considered feasible.